Does SIRT-1 Mediate Calorie Restriction and Prolong Life? – A Mini Review - Kordala Anna; Pietrzak Bogusława (Polish Journal of Food and Nutrition Sciences)
Calorie restriction is the only intervention proved to prolong both average and maximum lifespan in yeast, worms, fish, rodents and possibly primates. Not only does the regimen prolong life, but it also reduces the incident of numerous age-related diseases like diabetes, atherosclerosis or cancer and slows down ageing. Mechanisms by which that is thought to occur have not yet been elucidated, but they probably involve reactive oxygen species signaling, insulin growth factor and transcriptional factors. Here, special emphasis is given to SIRT1 - silent information regulator. There is sound evidence showing that SIRT1 is a key player in mediating physiological response to calorie restriction and that its overexpression is correlated with extended lifespan. The possible mechanism leading to its elevated levels is high NAD/NADH ratio, observed in Sir2 in yeast. SIRT1 increases glucose production, enhances fat mobilization, stimulates angiogenesis, prevents neuronal degeneration and rises insulin sensitivity. Therefore, it seems to be a very beneficial factor activated by such a simple intervention that is calorie restriction.